Effect of EDTA as washing solution on removing of heavy metals from sewage sludge by electrokinetic - Hanay, Ozge; Hasar, Halil; Kocer, Nilufer Nacar (Elsevier, 2009)
This paper presents the effect of ethylene diamine tetraacetic acid (EDTA) as a washing solution on the electrokinetic process for removal of Cr, Pb and Zn from sewage sludge. The sequential chemical extraction scheme according to the guidelines of BCR (Community Bureau of Reference) was applied to the sludge samples to evaluate the effect of EDTA on metal fractionation during electrokinetic processes. The highest removals of the heavy metals were 34% for Cr, 27% for Pb and 20% for Zn with 0.1 N EDTA. The removal priority of the metals by electrokinetic process was found to be Cr > Pb > Zn. According to the results of BCR analysis, addition of EDTA did not create the inter-transformation of Cr, Pb and Zn although the metal concentration decreased. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Electrokinetic; Heavy metal removal; BCR; EDTA; Sewage sludge